2020
DOI: 10.1016/j.jmmm.2019.166276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing on the electrical and magnetic properties of electrodeposited Ni and permalloy nanowires

Abstract: The influence of annealing on the microstructure and the electrical and magnetic properties of cylindrical nickel-based nanowires has been investigated. Nanowires of nickel of ~275 nm diameter and of permalloy (Py) of ~70 nm diameter were fabricated by electrochemical deposition into nanoporous templates of polycarbonate and anodic alumina, respectively. Characterization was carried out on as-grown and up to 650 °C heat-treated nanowires. Transmission electron microscopy imaging and diffraction of the nanowire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In particular, Tóth et al 52 investigated the effect of annealing at 300 °C for 1 h on the grain size of nanocrystalline CoNi alloys and found an increase from 10 to 40 nm for low Co contents. The experiment that is most similar to the present study was performed by Dost et al 63 , where annealing of 275 nmdiameter Ni nanowires at 650 °C for 1 h increased the grain size from 8 to 160 nm. TEM imaging also revealed that after annealing grains often occupied the entire diameter of the wire.…”
Section: Resultssupporting
confidence: 77%
“…In particular, Tóth et al 52 investigated the effect of annealing at 300 °C for 1 h on the grain size of nanocrystalline CoNi alloys and found an increase from 10 to 40 nm for low Co contents. The experiment that is most similar to the present study was performed by Dost et al 63 , where annealing of 275 nmdiameter Ni nanowires at 650 °C for 1 h increased the grain size from 8 to 160 nm. TEM imaging also revealed that after annealing grains often occupied the entire diameter of the wire.…”
Section: Resultssupporting
confidence: 77%
“…This could be explained by an uneven height distribution of the nanowires during the growth with some nanowires being taller than others. Microscopy techniques, such as SEM, have been widely used to study the morphology of nanowires deposited into nanoporous alumina templates (31)(32)(33)(34). Even if destructive preparation is required, such as focused ion beam milling, it is a very useful method for visualization of the nanowires inside of the template.…”
Section: Resultsmentioning
confidence: 99%
“…Microscopy techniques, such as SEM, have been widely used to study the morphology of nanowires deposited into nanoporous alumina templates [39][40][41][42]. Even if destructive preparation is required, such as focused ion beam milling, it is a very useful method for visualization of the nanowires inside of the template.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Tóth et al investigated the effect of annealing at 300 °C for 1 h on the grain size of nanocrystalline CoNi alloys and found an increase from 10 to 40 nm for low Co contents. The experiment that is most similar to this study was performed by Dost et al, where annealing of 275 nm diameter Ni NWs at 650 °C for 1 h increased the grain size from 8 to 160 nm. TEM imaging also revealed that after annealing grains often occupied the entire diameter of the wire.…”
Section: Resultsmentioning
confidence: 99%